Topics in Primary Care Medicine - Heston, Thomas F. (IntechOpen, 2021)
The medical specialty of primary care addresses the basic and fundamental healthcare needs of individuals, the family, and the larger community. Its reach starts at pre-conception and extends to global health and medical issues. Primary care issues include chronic medical problems, surgery, and community-wide health threats such as worldwide global pandemics, terrorism in all of its forms, and domestic violence. This book reviews eight topics including chronic medical issues like chronic fatigue syndrome, the response of primary care clinicians to global pandemics, and how patients and physicians are symbolized in comics. From top experts in the field, this book will improve your ability to practice primary care and to appreciate the broad demands placed upon primary care clinicians.